Epigallocatechin-3-Gallate Ameliorates Glucocorticoid-Induced Osteoporosis of Rats in Vivo and in Vitro - Shengye Liu; Liyu Yang; Shuai Mu; Qin Fu (Frontiers Media S.A., 2018)
Background: Prolonged administration of overdoses of glucocorticoids results in increased bone remodeling, leading to glucocorticoid-induced osteoporosis (GIO), which is primarily due to the dysfunction and apoptosis of osteoblasts. The present study investigated the therapeutic effect and molecular mechanism of action of epigallocatechin-3-gallate (EGCG), a bioactive catechin in green tea, in high-dose dexamethasone-induced osteoblast differentiation in vivo and in vitro.Methods: The anti-dexamethasone (DEX) effects of EGCG on primary osteoblasts were determined on the basis of cell viability and alkaline phosphatase (ALP) and total cellular superoxide dismutase (SOD) activities. Flow cytometry and Western blot analysis were also used to evaluate the expression of related biomarkers in vitro, and bone microarchitecture was also extensively examined in a rat model in vivo.Results: The results showed that EGCG pretreatment significantly increased osteoblast viability and ALP and SOD activities when cells were exposed to DEX. Alizarin red staining indicated that there was more mineralization with EGCG pretreatment, countering DEX effects. EGCG reduced DEX-induced reactive oxygen species at both the mitochondrial and cellular levels in osteoblasts by activating the nuclear factor erythroid-derived 2-like-2 (Nrf2) pathway. In addition, EGCG protected osteoblasts from apoptosis. EGCG also regulated the formation of active glucocorticoid by 11β-hydroxysteroid dehydrogenase activity. Furthermore, femoral micro-computed tomography scans revealed that EGCG improved bone microstructure and mitigated DEX-induced deterioration of bone quality.Conclusion: These findings suggested that EGCG reversed GIO in rats by protecting osteoblasts by activating the Nrf2 signaling pathway.